2018
DOI: 10.1371/journal.pcbi.1006430
|View full text |Cite
|
Sign up to set email alerts
|

Network mechanisms underlying the role of oscillations in cognitive tasks

Abstract: Oscillatory activity robustly correlates with task demands during many cognitive tasks. However, not only are the network mechanisms underlying the generation of these rhythms poorly understood, but it is also still unknown to what extent they may play a functional role, as opposed to being a mere epiphenomenon. Here we study the mechanisms underlying the influence of oscillatory drive on network dynamics related to cognitive processing in simple working memory (WM), and memory recall tasks. Specifically, we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 60 publications
5
88
0
Order By: Relevance
“…We focused here on sinusoidal forcing of bump solutions, which is a proxy of oscillations ubiquitous in neuronal systems. In previous work 26 , the neural mass version of this model was studied in terms of its response to oscillatory forcing in various frequency bands, and the present paper makes this exploration feasible also in the spatially-extended model. We leave this exploration to a future publication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused here on sinusoidal forcing of bump solutions, which is a proxy of oscillations ubiquitous in neuronal systems. In previous work 26 , the neural mass version of this model was studied in terms of its response to oscillatory forcing in various frequency bands, and the present paper makes this exploration feasible also in the spatially-extended model. We leave this exploration to a future publication.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting we expect oscillons to emerge without bifurcation from a localised steady state of the QIF mean field model with A = 0, upon imposing a small-amplitude forcing, A 1. We therefore select the default kernel (5), set η = −10, for which the model with A = 0 supports one stable (wide) and one unstable (narrow) bump (see Figure 3), and continue time-periodic solutions to (25) in A > 0 for ω = 4, close to the network's resonant frequency 26 .…”
Section: A Oscillons Induced By Harmonic Forcingmentioning
confidence: 99%
See 1 more Smart Citation
“…These regimes could be well traversed via transient inputs, as depicted in Figure 4B. Driving the microscopic model given by (2) and (20)(21)(22)(23) with the same transient inputs, we found that the spiking dynamics were still attracted to the low-dimensional manifold described by the macroscopic system. This shows, that even with τ A = 10τ , the condition τ A τ is sufficiently satisfied for the macroscopic description of the population bursting dynamics to be valid.…”
Section: Ivb Effects Of Sfamentioning
confidence: 78%
“…Forη, the parameter range in which the limit cycle exists corresponds to most of the cells in the population being in an excitable regime and has been reported for a number of models using QIF neurons (e.g. 15,22,23 ). Within this range, the inter-burst period can be varied from 13τ up to 105τ via changes in α andη (see Figure 3B).…”
Section: Iiic Limit Cycle Characteristicsmentioning
confidence: 85%